2003
DOI: 10.1016/s0378-1097(03)00740-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and identification of tetracycline-resistant oral bacteria in children not receiving antibiotic therapy

Abstract: The prevalence of tetracycline-resistant oral bacteria in healthy 4- and 6-year-old children who had not received antibiotics during the 3 months prior to sampling was investigated. Of the 47 children sampled, 46 harboured tetracycline-resistant bacteria. The median proportion of cultivable anaerobic and aerobic oral bacteria resistant to tetracycline was 1.1% and the MIC50 of these was 64 microg ml(-1). The majority (56%) of tetracycline-resistant bacteria were resistant to at least one other antibiotic, usua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
25
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 33 publications
5
25
0
Order By: Relevance
“…The oral cavity harbors a diverse community of microorganisms and has been shown to be a reservoir for antibiotic-resistant bacteria (5,9,14). The most widespread tetracycline resistance (Tc r ) gene identified from oral bacteria is tet(M) (9,17,19). It has been identified in 42 genera (16) and is usually found on conjugative transposons of the Tn916/ Tn1545 family (4).…”
Section: ؊5mentioning
confidence: 99%
“…The oral cavity harbors a diverse community of microorganisms and has been shown to be a reservoir for antibiotic-resistant bacteria (5,9,14). The most widespread tetracycline resistance (Tc r ) gene identified from oral bacteria is tet(M) (9,17,19). It has been identified in 42 genera (16) and is usually found on conjugative transposons of the Tn916/ Tn1545 family (4).…”
Section: ؊5mentioning
confidence: 99%
“…Therefore, it is becoming recognized that commensal bacteria likely play a key role in the evolution and dissemination of genetic elements, including AR genes, in microbial ecosystems (2,18,22,25,33,36,37). While the large AR gene pools in food animals, lagoon water, and farm manures (1,6,13,25,29,34) might be related to exposure to growth-promoting antibiotics, the high prevalence of ART bacteria in oral and fecal samples from healthy human subjects and wild animals without a recent history of antibiotic exposure (3,9,11,14,28,30,32) suggests that there might be major knowledge gaps regarding AR acquisition and circulation pathways involving human and animal hosts. In fact, recent studies revealed a large number and broad spectrum of food-borne ART commensal bacteria with resistance-encoding genes in conventional retail foods, including many ready-to-consume items, suggesting that humans are constantly exposed to ART bacteria through daily food intake (8,16,37).…”
mentioning
confidence: 99%
“…is the most extensively studied antibiotic resistance gene in terms of molecular ecology 9) and has been found among numerous species of Gram-negative and Gram-positive bacteria including not only human pathogens 6,20,22,38) but also bacteria obtained from several terrestrial environments associated with human activity 9) such as in agriculture 33) , groundwater 8) , and daily diets 14,16,26,39) . Tet(M) is often accompanied by mobile elements such as plasmids and transposons, such associations contributing to the wide distribution of this gene in bacterial genera obtained from different environments 9) .…”
mentioning
confidence: 99%